Electronic Accounting Services and their Effect on Enhancing the Efficiency of Financial Institutions (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2021)
The paper focuses on how electronic accounting services can be enhanced in financial institutions by analyzing the quality of the electronic accounting system used by financial institutions, including the banking sector in the Kurdistan region of Iraq. Additionally, how the electronic accounting services affected the growth of financial reporting. Research enables management to realize the need to develop accurate and high-quality financial data through accounting software packages. The community sample consisted of 60 male and female employees distributed among three private sector financial institutions. This type of sampling is believed to be neither random nor biased at the same time, and the survey method used is descriptive as well as inferential statistics. The hypotheses were tested through this research. It is all clear that electronic accounting services have a significant impact on the efficiency of financial institutions' work due to their impact of the internal control system. The results of the research showed that although there is no direct impact between the internal control system and the general financial efficiency of financial institutions, there are indications on some elements of the internal control system that show this effect, such as risk assessment and control activities with elements from a financial perspective such as profitability, efficiency and liquidity.The paper also reveals that financiers and accountants have been routinely trained by the certified staff of the company to protect their expertise in the event of adjustments or accounting difficulties. The findings of this paper recommend a number of suggestions, including the need for further internal control investigations to determine and analyze the effectiveness of controls in financial institutions in the Kurdistan region of Iraq, as defined in the accounting framework.